A proposed "integrated-adaptive" behavioral model for women entrepreneurs: The Philippine experience - Malaya, Milagros F. (Animo Repository, 2024)
This study investigates firm performance by adopting a gendered perspective using the Brush (1992) Integrated Perspective framework. The relationship between gender and firm performance was indicated in terms of the possible direct and indirect (moderating) effects of gender on performance through its impact on the different management factors (style and strategies). The findings in this study imply that certain differences between men and women owners seem to be more fundamental in nature. In addition to providing support for women's "integrated perspective" in managing a business, evidence strongly suggests that women exhibit "adaptive" behavior as opposed to men's "consistent" behavior.